2022
DOI: 10.3390/pharmaceutics14010198
|View full text |Cite
|
Sign up to set email alerts
|

Swallowability of Minitablets among Children Aged 6–23 Months: An Exploratory, Randomized Crossover Study

Abstract: Minitablets have garnered interest as a new paediatric formulation that is easier to swallow than liquid formulations. In Japan, besides the latter, fine granules are frequently used for children. We examined the swallowability of multiple drug-free minitablets and compared it with that of fine granules and liquid formulations in 40 children of two age groups (n = 20 each, aged 6–11 and 12–23 months). We compared the percentage of children who could swallow minitablets without chewing with that of children who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
3
2
0
Order By: Relevance
“…The results of a previous study suggested that mini-tablets may only be suitable for children from 4 years old [ 11 ]. However, the present results suggest that mini-tablets could be a feasible and safe method of drug administration for children as young as 2 years old and are in line with the findings of other studies, including studies that have demonstrated the acceptance of mini-tablets by very young children, including newborns and infants 6 months to 1 year old [ 10 , 12 , 13 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…The results of a previous study suggested that mini-tablets may only be suitable for children from 4 years old [ 11 ]. However, the present results suggest that mini-tablets could be a feasible and safe method of drug administration for children as young as 2 years old and are in line with the findings of other studies, including studies that have demonstrated the acceptance of mini-tablets by very young children, including newborns and infants 6 months to 1 year old [ 10 , 12 , 13 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Parents of children 0–<2 y preferred mini-tablets over syrup, and parents of children 2–<6 y preferred mini-tablets (different amounts) and the lower quantity of syrup over the higher syrup volume. These results are in line with the preferences for future drug applications expressed by parents of children between the ages of 6 and 11 months in another study [ 23 ].…”
Section: Discussionsupporting
confidence: 89%
“…This preference was consistent among all stakeholders, despite some differences in formulation preferences of different stakeholders for the four age groups of pediatric patients. This very important result is in line with several other investigations and studies [ 8 , 9 , 10 , 11 , 12 , 14 , 15 , 16 , 17 , 18 , 23 ] and contrasts with the current practice of administering medicines to children aged 0–<6 y as a liquid formulation. As syrups or other liquid formulations might contain excipients with potential toxicological risks [ 35 ], a switch to alternative dosage forms could not only increase the acceptability but also improve the risk profile.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In Japan, powder and fine granules are popular pediatric dosage forms [ 2 ]; however, their taste and roughness present difficulties [ 7 ]. Mini-tablets can circumvent problems associated with syrups, powders, and fine granules, making them easy to develop globally; however, studies on the dosing and acceptability of mini-tablets in pediatric patients have only been conducted using a placebo [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%